Perfil bioquímico de frangos de corte experimentalmente intoxicados com aflatoxina com e sem a adição de montmorilonita sódica na dieta alimentar. - Batina, Patricia Neves (2004)
This research had as objective evaluated the biochemistry values and the hepatic and renal enzymatic activity pf broiler chicken submitted to experimental intoxication using aflatoxin with and without addition of sodic montmorilonite on the diet. In this study were used 528 Cobb s broiler chickens that were divided in 6 treatments from 1º to 42º day of life: (T1) control: normal diet; (T2) diet with 5 ppm of aflatoxin; (T3) diet with 0,25% sodic montmorilonite; (T4) diet with 5 ppm of aflatoxin + 0,25% sodic montmorilonite; (T5) diet with 0,50% sodic montmorilonite; (T6) diet with 5 ppm of aflatoxin + 0,50% sodic montmorilonite. The treatment (T2) showed significant (P<0.01) decreased levels of uric acid, albumin, cholesterol, creatinine, triglycerides, globulins and total serum proteins. There was statistically significantly increased on alanine aminotransferase (ALT). Aspartate aminotransferase (AST) did not show up important differences among treatments. In (T3) and (T5) there was not variation on the biochemical values when compared with treatment (T1). The sodic montmorilonite (0,50%) (T6) presented the better results on the reduction of the aflatoxin s adsorption when compared with the sodic montmorilonite from (0,25%) (T4). The outcome of this experiment proposed that high level of diet aflatoxin does cause important biochemistry changes on the enzymatic activity of the broiler chicken and also the alternative treatments using sodic montmorilonite may be used to avoid risks caused by feed contamination by aflatoxins.